ENHANCING CAFÉ HOPPING EXPERIENCE THROUGH MOBILE APPLICATIONS - Huang, Chua Li (Universiti Malaysia Sarawak(UNIMAS), 2019)
“Hop” is a mobile application which is specifically created for the users to enhance their experience while visiting any café. This study is created based on the problems and experiences faced by café lovers. The design is focused on the interface and user experience which may assist the user with different kinds of experience.